2017
DOI: 10.1139/cjfas-2016-0500
|View full text |Cite
|
Sign up to set email alerts
|

Internal phosphorus loading in Canadian fresh waters: a critical review and data analysis

Abstract: Many physical, chemical, and biological processes in freshwater ecosystems mobilize the nutrient phosphorus (P) from sediments, which in turn may contribute to the formation of harmful algal blooms. Here, we critically reviewed internal P loading in Canadian fresh waters to understand the geographic patterns and environmental drivers of this important process. From 43 publications, we consolidated 618 estimates of internal P loading from Canadian freshwater ponds, lakes, reservoirs, and coastal wetlands (n = 7… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

10
148
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 195 publications
(158 citation statements)
references
References 273 publications
10
148
0
Order By: Relevance
“…Support for this hypothesis occurs if water or summer air temperature is an important predictor of HABs with a positive drift coefficient. Longer summer : Longer seasons of high temperature increase the opportunity for cyanobacterial growth (Anneville et al ; Deng et al ; Visser et al ). Support for this hypothesis occurs if spring air temperature is an important predictor of HABs with a positive drift coefficient. Internal phosphorus loading : Higher temperature increases the rate of internal phosphorus loading, driving HABs (Jeppesen et al ; Matisoff et al ; Orihel et al ; Ding et al ). Support for this hypothesis occurs if water or summer air temperature is an important predictor of TP with a positive drift coefficient, and TP is an important predictor of HABs with a positive drift coefficient. Load driving : Greater precipitation amounts increase nutrient loading, driving HABs (Reichwaldt and Ghadouani ; Michalak et al ).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Support for this hypothesis occurs if water or summer air temperature is an important predictor of HABs with a positive drift coefficient. Longer summer : Longer seasons of high temperature increase the opportunity for cyanobacterial growth (Anneville et al ; Deng et al ; Visser et al ). Support for this hypothesis occurs if spring air temperature is an important predictor of HABs with a positive drift coefficient. Internal phosphorus loading : Higher temperature increases the rate of internal phosphorus loading, driving HABs (Jeppesen et al ; Matisoff et al ; Orihel et al ; Ding et al ). Support for this hypothesis occurs if water or summer air temperature is an important predictor of TP with a positive drift coefficient, and TP is an important predictor of HABs with a positive drift coefficient. Load driving : Greater precipitation amounts increase nutrient loading, driving HABs (Reichwaldt and Ghadouani ; Michalak et al ).…”
Section: Methodsmentioning
confidence: 99%
“…This occurs through increased growth rates of harmful cyanobacterial species relative to other species (Paerl and Huisman ; Carey et al ; Visser et al ), through extending of the summer growing season (Anneville et al ; Deng et al ; Visser et al ) and through increased vertical stratification resulting in greater fitness by cyanobacteria that are able to regulate their buoyancy (Wagner and Adrian ; Carey et al ; Posch et al ; Taranu et al ; Visser et al ). Higher temperature also increases internal phosphorus loading from sediments through increased rates of soil diffusivity and increased rates of soil phosphorus regeneration (Matisoff et al ), and this internal phosphorus source has been shown be a significant proportion of the overall phosphorus budget in some lakes (Jeppesen et al ; Ho and Michalak ; Orihel et al ; Ding et al ). Second, greater overall precipitation and more extreme precipitation events are hypothesized to increase HABs through the generation of greater nutrient runoff (Reichwaldt and Ghadouani ; Michalak et al ), although this could be balanced by greater precipitation flushing nutrient‐rich waters out of the ecosystem prior to bloom formation (Anderson et al ; Reichwaldt and Ghadouani ).…”
mentioning
confidence: 99%
“…After decades of sustained external P inputs, lakes have been shown to accumulate legacy P and experience mobilization of P from the sediment (i.e., internal loading), a phenomenon extensively reviewed in the literature (e.g., Orihel et al, ). Internal P load is a significant concern for stakeholders due to continued water quality deterioration, with associated social and economic costs, and despite measures put in place to reduce external P loads (Matisoff et al, ; Mueller et al, ).…”
Section: Introductionmentioning
confidence: 99%
“…After decades of sustained external P inputs, lakes have been shown to accumulate legacy P and experience mobilization of P from the sediment (i.e., internal loading), a phenomenon extensively reviewed in the literature (e.g., Orihel et al, 2017). Internal P load is a significant concern for stakeholders due to continued Process-oriented lake modeling is a useful tool for guiding and assessing long-term management and water governance strategies.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation